The influencing factors of the consumers’ propensity to support Multilevel Marketing businesses in Malaysia - Wong, Lun Cheng (2017)
Purpose-As a result of the increasing living pressure in a competitive society, the direct-selling or multilevel marketing (MLM) business appears as an appealing platform for many who seek to attain the so-called financial freedom (Bloch, 1996). This has led to the boom in the MLM industry, where many are now solely depending on the MLM business as their main source of income. Apart from joining membership, there is also a growing tendency in the purchase of MLM products. Thirdly, despite the controversies and negative repercussion that have been evoked by both MLM and pyramiding companies, many Malaysians still support the business. This paper therefore aims to discover the influencing factors of the Malaysians’ propensity to purchase, join, and even like the MLM business. In addition to that, a specific test on the Malaysians overall perception on the ethical issues of MLM was conducted. Methodology/design– The sample of this research comprised of 152 Malaysians who are mainly based in Kuala Lumpur. The author has personally administered an online questionnaire to collect reliable scale data in order to construct a valid research model: from the Overall support (buy, join, like) to the 6 independent variables affecting one to support MLM businesses. Findings – The results show that 5 independent variables have a significant influence on one’s propensity to support the MLM business except for the variable Company_factors. Among those significant variables, only Cognition level has a negative association with the dependent variable Overall Support. Business implications – MLM organizations have to focus on developing and refining the product element in the marketing mix rather than focusing on network expansion. Secondly, the MLM businesses need to form an ecosystem of interdependency and mutual benefits between the firm, its distributors and the customers in order to sustain the business for the long-run.